A Scoping Review of the Evidence regarding Assessment and Management of Psychological Features of Shoulder Pain. (30th September 2021) - Farzad, Maryam; MacDermid, Joy C.; Ring, David C.; Shafiee, Erfan
Abstract : Background and Aim . Shoulder pain is second only to low back pain among costs associated with the care of musculoskeletal disorders. Psychological factors, social factors, and mental health can contribute to shoulder pain and resulting functional disability. The purpose of this scoping review was to identify the nature of the research that has integrated psychological assessment and treatment in the management of shoulder pain. Methods . A scoping review of research studies identified through PubMed, EMBASE, and CINAHL and graduate theses identified using Google Scholar was conducted to determine studies and systematic reviews that addressed the management of psychological aspects of shoulder pain with or without neck pain. The search terms included psychological factors, anxiety, depression, catastrophic thinking, fear of movement, and psychological treatments. Two investigators screened study titles and abstracts. Data extraction, content analysis, and thematic coding focused on the dimensions of pain addressed (emotional, behavioural, and cognitive) and treatment approaches used (dimensions targeted, specific treatment parameters) and the linkage between treatment targets/rationale with interventions/outcomes measured. Results . Ten studies (seven randomized trials and three cohorts) were identified that addressed the psychological aspects of shoulder pain. Out of seven RCTs, four compared psychological interventions with usual care. Eight studies used cognitive approaches, including emotional freedom techniques (EFT), pain coping strategies (PCS), physical-cognitive-mindfulness training (PCMT), psychological flexibility, face-to-face cognitive-behavioural treatment (CBT), and cognitive therapy using virtual reality (V.R.). Three studies used the behavioural approaches as their intervention, including behavioural therapy and Graded Exercise Therapy (GET). Pain intensity was addressed as the primary outcome in two studies and as a secondary outcome in five studies. Cognitive factors were evaluated in 50% of the articles using nine different measures. Emotional factors were evaluated in 80% of articles using ten different measures. Reduction of pain intensity and catastrophic thinking concerning pain was achieved in most studies using a biopsychosocial approach (70%). Applying a behavioural approach was associated with reductions in kinesiophobia and pain catastrophizing. Cognitive approaches had a positive association with reductions in the emotional aspect of pain. Only one study specifically linked rationale or specific physical and psychosocial treatment targets with the treatments provided and outcomes measured. Conclusions . Small pools of studies indicate that the rationale and treatment targeting are poorly defined in biopsychosocial interventions for shoulder pain. However, these benefits have been demonstrated when cognitive or behavioural components are added to the standard physical treatment of shoulder pain. A better definition of treatment targets, description of intervention components, and linkage of outcomes to targets are needed to advance our understanding of optimizing bio-psychosocial approaches.